Praktik Sosial Nongkrong pada Kalangan Pemuda di Kawasan Tanjung Dapura Kota Makassar - Emanuel Omedetho Jermias; Abdul Rahman (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
The The existence of cafes in Makassar City has been able to drive the economy of micro, small and medium enterprises and become a hangout place for young people. This study attempts to explore the meaning of young people regarding hanging out at C6-Coffee and the relationship between hanging out as a social practice in a third place. The study uses a qualitative method, namely data collection is carried out by means of observation and interviews, then the data is analyzed through data reduction, data presentation, and drawing conclusions. The results of the study show that hanging out at cafes is interpreted positively by young people because it is used as an arena for self-actualization and developing human resource capacity. Hanging out at cafes for young people is a social practice that utilizes the third space after home and campus. The meaning of young people towards cafes as a third space has spurred them to do positive things such as studying, strengthening social solidarity, and developing networks that can be constructed as part of cultural capital.